“When our words are put to paper.” Heritage documentation and reversing knowledge shift in the Bering Strait region - Krupnik, Igor (Études/Inuit/Studies, 2005)
AbstractThe paper examines the relationship between indigenous knowledge and heritage documentation efforts generated by scientists and other forms of local activities that work in strengthening indigenous cultural identity and tradition. As the studies in indigenous heritage and environmental knowledge have become one of the fastest-growing fields in northern cultural research, there is tough competition for limited resources and, even more, for the time, goodwill, and attention of northern constituencies. Scholarly projects in heritage and knowledge documentation represent just one stream within today's public efforts, though an important and visible one. Those projects do have an impact in local communities; but such impact is often subtle, circumstantial, and may not be sustainable when left standing on its own. Local knowledge, very much like active language, relies primarily on oral transmission, family ties, community events, and subsistence activities. As long as those prime channels of cultural continuity are working, “our words put to paper”—knowledge and heritage sourcebooks, school materials, and catalogs—should be regarded as long-term cultural assets that may play a crucial role in the transformed northern societies of today and of tomorrow.